“I want Black children to know that they should never, ever, ever settle for things that society wants to give to them”: Self‑published Black French and Black German Children’s Literature as Blacktivism - Malanda, Élodie (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
In this paper, I analyze self‑published children’s books by Black French and Black German authors as a form of Blacktivism. I study how the authors’ comments about their work echoes with an activist narrative, and how they participate in a fight for racial justice, not only through the message of their children’s books, but through their choice of self‑publishing. First, I examine their motivations for writing and relate them to what I call “kidliteractivism,” to then show how self‑publishing can be a form of literary and racial insubordination, and finally I shed light on how self‑published children’s books by French and German authors of African descent are linked to broader Blacktivist movements in France and Germany.